2023
DOI: 10.1371/journal.pone.0287399
|View full text |Cite
|
Sign up to set email alerts
|

Genotype profiles of high-risk human papillomavirus in women of reproductive age: A community-based study

Dewi Wulandari,
Reiva Wisdharilla Meidyandra,
Andrijono

Abstract: Purpose This research is a preliminary study to observe the high-risk HPV infection profile among asymptomatic women, as a basis for developing Indonesian-specific reagents and implementing a national vaccination program. Methods The research subjects were female employees/families of BUMN (state-owned enterprises) who underwent annual routine medical check-up. The research sample was a cervical swab which was examined using the Cobas® 6800 platform for HPV identification and INNO Lipa (Fujirebio) kit for id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…High-risk and low-risk HPV co-infection in immunosuppressed individuals may be due to more rapid viral replication or reactivation of latent infection (Setyowati, et al 2020). The results are in line with Wulandari et al [14] which states that genotype 52 is the most frequently found genotype. These results also support Wulandari et.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…High-risk and low-risk HPV co-infection in immunosuppressed individuals may be due to more rapid viral replication or reactivation of latent infection (Setyowati, et al 2020). The results are in line with Wulandari et al [14] which states that genotype 52 is the most frequently found genotype. These results also support Wulandari et.…”
Section: Resultssupporting
confidence: 92%
“…These results indicate that there are more HPV genotypes than Wulandari et al [14]. Meanwhile, this research only took samples in Jakarta, compared to Wulandari et al [14] who collected samples from Jakarta as well as Bogor, Bandung and Semarang and the number of samples almost doubled (> 800), using cervical swab sample media. These differences may also be caused by differences in sample processing methods.…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations